Echocardiographic Changes Following Surgical Myectomy in Severely Symptomatic Obstructive Hypertrophic Cardiomyopathy: Insights From the SPIRIT‐HCM Study - Milind Y. Desai; Natalie Szpakowski; Albree Tower‐Rader; Barb Bittel; Agostina Fava; Susan Ospina; Bo Xu; Maran Thamilarasan; Amgad Mentias; Nicholas G. Smedira; Zoran B. Popovic (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background In obstructive hypertrophic cardiomyopathy, myectomy improves symptoms, quality of life, and left ventricular (LV) outflow tract gradients. We prospectively evaluated the temporal changes in various echo parameters after myectomy. Methods and Results In 173 adults with obstructive hypertrophic cardiomyopathy (53±10 years, 63% men) who underwent myectomy between March 2017 and June 2020, clinical and blinded echo assessment (before and at 12±6 months follow‐up) was performed prospectively (SPIRIT‐HCM [Quality of Life and Functional Capacity Following Septal Myectomy in Obstructive Patients With Hypertrophic Cardiomyopathy]). Changes in echocardiographic parameters (left atrial volume index, E/e′, LV outflow tract gradients, along with average LV global longitudinal strain on apical 2‐, 3‐, and 4‐chamber views and regional LV strain from apical 4‐chamber view) were measured in 126 patients. There was significant improvement in left atrial volume index (−6.9 mL/m2 [95% CI, 4–9.7]), E/e′ (−2.9 [95% CI, −2.7 to −4.1]) and peak LV outflow tract gradient (−94 mm Hg [95% CI −87 to −100]) from baseline to follow‐up (both P<0.001). There was no improvement in basal (0.91% [95% CI, −0.15 to 1.97], P=0.09) and midseptal (−0.98% [95% CI, −1.93 to 0.02], P=0.05) LV strain, worsening in apical septal strain (−4.5% [95% CI, −5.9 to −3.0], P<0.001) and an improvement in LV free wall strain (2.3% [95% CI, 0.67–3.9], P<0.001), with no change in overall LV‐global longitudinal strain (0.47% [95% CI, −0.43 to 1.37], P=0.30). There was no correlation between change in LV‐global longitudinal strain and change in 6‐minute walk time (r=0.12, P=0.24) or Kansas City Cardiomyopathy Questionnaire summary score change (r=0.02, P=0.85), whereas it was significantly associated with change in E/e′ (r=0.29, P=0.003). Conclusions In patients with obstructive hypertrophic cardiomyopathy, myectomy improved various echocardiography parameters at 1‐year; however, LV‐global longitudinal strain remained unchanged. Registration URL: https://clinicaltrials.gov; Unique identifier: NCT03092843.